Alkanolamine-Grafted and Copper-Doped Titanium Dioxide Nanosheets–Graphene Composite Heterostructure for CO2 Photoreduction - Apisit Karawek; Nutkamol Kitjanukit; Wannisa Neamsung; Chonlathon Kinkaew; Poomiwat Phadungbut; Panpailin Seeharaj; Pattaraporn Kim‐Lohsoontorn; Sira Srinives (ACS Applied Energy Materials, 2023)
CO2 photoreduction is an intriguing approach to carbon capture, utilization, and storage (CCUS). It relies on an effective photocatalyst to generate photoinduced electrons that incorporate carbon dioxide (CO2), yielding fuel products, e.g., methane, methanol, and ethanol. The heterostructure of titanium dioxide nanosheets (TNS) and graphene oxide (GO) is a sandwich-type composite consisting of two 2-dimensional nanostructures (2D–2D). It was demonstrated as an excellent candidate for CO2 photoreduction due to its outstanding charge separation ability. This research studied the photoactivity of alkanolamine-grafted TNS and alkanolamine-grafted and copper-doped TNS/GO composites. In the first experiment, triethanolamine-grafted TNS (TEA–TNS) exhibited the best ability in CO2 photoreduction compared to monoethanolamine- and diethanolamine-grafted TNS (MEA–TNS and DEA–TNS) due to the base-catalyzed hydration nature of CO2–TEA interactions. In the second experiment, we studied the photoactivity of four composites, including copper-doped TNS/GO (Cu-TNS/GO), TEA-[Cu-TNS/GO] (grafting TEA on Cu-TNS/GO), Cu-[TEA-TNS]/GO (doping Cu on TEA-TNS/GO), and TEA-Cu-TNS/GO (one-step hydrothermal synthesis with the Cu precursor, TEA, and GO). TEA-[Cu-TNS/GO] showed the best photoactivity since TEA was added last to the heterostructures, which benefited in avoiding side chelation reactions between TEA and Cu ions and ensuring TEA exposure to CO2.
Keywords: Advanced Photocatalysis Techniques; CO2 Reduction Techniques and Catalysts; Covalent Organic Framework Applications